Cofactor‐Assisted Artificial Enzyme with Multiple Li‐Bond Networks for Sustainable Polysulfide Conversion in Lithium–Sulfur Batteries. Issue 3 (7th November 2021) - Zhou, Suya; Yang, Shuo; Cai, Dong; Liang, Ce; Yu, Shuang; Hu, Yue; Nie, Huagui; Yang, Zhi
Abstract: Lithium–sulfur batteries possess high theoretical energy density but suffer from rapid capacity fade due to the shuttling and sluggish conversion of polysulfides. Aiming at these problems, a biomimetic design of cofactor‐assisted artificial enzyme catalyst, melamine (MM) crosslinked hemin on carboxylated carbon nanotubes (CNTs) (i.e., [CNTs–MM–hemin]), is presented to efficiently convert polysulfides. The MM cofactors bind with the hemin artificial enzymes and CNT conductive substrates through FeN5 coordination and/or covalent amide bonds to provide high and durable catalytic activity for polysulfide conversions, while π – π conjugations between hemin and CNTs and multiple Li‐bond networks offered by MM endow the cathode with good electronic/Li + transmission ability. This synergistic mechanism enables rapid sulfur reaction kinetics, alleviated polysulfide shuttling, and an ultralow (<1.3%) loss of hemin active sites in electrolyte, which is ≈60 times lower than those of noncovalent crosslinked samples. As a result, the Li–S battery using [CNTs–MM–hemin] cathode retains a capacity of 571 mAh g −1 after 900 cycles at 1C with an ultralow capacity decay rate of 0.046% per cycle. Even under raising sulfur loadings up to 7.5 mg cm −2, the cathode still can steadily run 110 cycles with a capacity retention of 83%. Abstract : A cofactor‐assisted artificial enzyme with multiple Li‐bond networks, melamine (MM) crosslinked hemin on carboxylated carbon nanotubes (CNTs) ([CNTs–MM–hemin]), as a catalyst is introduced into lithium–sulfur (Li–S) batteries. The [CNTs–MM–hemin]‐based cathode significantly accelerates the sulfur redox reaction kinetics and suppresses the polysulfide shuttle, thereby improving the electrochemical performance of Li–S batteries remarkably, even under high sulfur loadings.